Eastern And Western Perspectives : Strategy And Special Operations - Leong, Adam Kok Wey (UPNM Press, 2021)
Clearly demonstrates that there is no such Western or Eastern divide in special operation warfare. Human are born with the innate nature to flight wars in the most economical and efficient manner. Not surprisingly, human from all cultures are naturally inclined to practice similar maxims in order to win wars economically and efficiently